Food Poisoning as Rights Neglect: State Accountability in Indonesia's Free Nutritious Meal Program (MBG) Under Child Protection Law - Ade Yuni Ratnasari; Dadang Sundawa; Syaifullah (Edueksos: Jurnal Pendidikan Sosial & Ekonomi, 2026)
The Free Nutritious Meal Program (MBG) is a public policy designed to guarantee children's rights to adequate health and nutrition under Law Number 35 of 2014 on Child Protection. However, since its launch in January 2025, the program has been marked by widespread food poisoning cases, with CELIOS research recording over 15,000 cases through November 2025. Although food safety and children's rights have been studied separately, no comprehensive legal analysis has examined Free Nutritious Meal Program poisoning cases as a form of neglect of children's rights and its implications for state accountability. This study aims to analyze forms of rights neglect in Free Nutritious Meal Program poisoning cases and map legal responsibilities based on the best interests of the child principle. Normative legal research was employed using statute and conceptual approaches. Data consisted of primary, secondary, and tertiary legal materials collected through library research and analyzed qualitatively using a descriptive-analytical method. Findings reveal that MBG poisoning cases constitute neglect of children's rights to survival and development, physical and mental health, education, protection from negligence, and the best interests of the child principle. Legal responsibility extends to the state, the National Nutrition Agency, Nutrition Fulfillment Service Units, schools, and local governments. Recurrent poisoning cases reflect systemic weaknesses in oversight, food safety standards, and accountability mechanisms. This study implies the urgent need for strengthened legal accountability, risk-based monitoring reform, and child rights-centered policies to prevent recurrence.